A comparison of the burden and resultant risk associated with occupational falls from a height and on the same level in Australia. Issue 12 (1st December 2016) - Mangharam, Jean; Moorin, Rachael; Straker, Leon
Abstract: Occupational falls are one of the leading causes of occupational injury and death internationally. This study described the nature of occupational falls following an analysis of workers compensation data in Western Australia. Frequencies, proportions and incidence rates were calculated following mechanism, gender, age and industry stratification. The natures of injury and bodily locations affected were compared between mechanisms of fall. Industry incidence rates were ranked and their corresponding proportions reported. Cost and lost time were described and risk scores for each burden type (incapacity, cost and lost time) were calculated and compared between fall mechanisms. Of all occupational falls, the proportion, incidence rates and risk scores of falls on same level were consistently greater compared to falls from a height. Gender, age and industry groups that appear to be at highest risk vary with the measure used and mechanism of incident. This study translates epidemiological information into a risk score that can aid in prioritisation. Practitioner Summary : This paper presents an in-depth analysis of Worker's Compensation claims for falls in Western Australia. Calculated proportion, incidence rates and formulated risk scores for falls on the level were consistently greater compared to falls from a height. Limitations associated with the analysis of large-scale data-sets are described.